Phenotypic characterization and documentation of Gaddi dog of western Himalayan region of India - SANKHYAN, VARUN; THAKUR, RAKESH; DOGRA, P K; THAKUR, ANKAJ (The Indian Journal of Animal Sciences, 2022)
India has the privilege of having excellent dog populations, but efforts to recognize them as distinct breeds are far and wide. The present study was designed to undertake the phenotypic characterization of Gaddi dogs, in Himalayan region of the state of Himachal Pradesh, India. The approach used was to gather as much information available on Gaddi dogs from communities involved in their traditional rearing. Though, many anecdotal evidence about its origin exists, the most plausible relates it to the development of this distinct breed by Gaddi shepherds during migration in Himalayan ranges. The Gaddi dogs are predominately black with occasional white marking on the feet, tail, or trunk region. One of their main attributes is their massive, arched neck that protects them from predators. These dogs have harmonious build, medium stature, moderately long, robust muscular body. In bitches, age at first estrus ranged from 12-18 months with main breeding season from September to November. The number of whelping in a lifetime was reported to be 8-12 with a litter size of 4-8 pups. Shepherds usually do not follow a strict vaccination or deworming schedule of the dogs and housing is also not provided. The dog is primarily developed and used for the herding of sheep and goats by shepherds of the Gaddi tribe. These shepherds must be rewarded and encouraged to maintain the purity of the breed. The present study paved the way for recognition of the Gaddi dog and highlighted the headway options for its conservation and propagation.